The interaction between common genetic mutations in AML and the immune landscape: mechanisms and implications for immune response - Guo, Xuege; Zhang, Hanlu; Wang, Xiao; Li, Lijuan; Zhang, Liansheng (Frontiers in Immunology, 2025)
Acute myeloid leukemia (AML) is a heterogeneous hematologic malignancy driven by diverse genetic mutations that shape tumor progression, immune evasion, and clinical outcomes. While molecular profiling has improved AML classification, the precise impact of specific mutations on immune cell infiltration and dysregulation remains insufficiently understood. This review examines the immunologic consequences of common AML mutations—including FLT3-ITD, NPM1, DNMT3A, TP53, IDH1/2, and NRAS—and their role in remodeling the immune microenvironment. We further explore the dynamic shifts in immune responses across different AML risk stratifications, emphasizing the balance between immune activation and suppression, which is influenced by specific genetic alterations. Additionally, we highlight the emerging potential of immunotherapies targeting neoepitopes derived from driver mutations, offering promising avenues to overcome immune escape and enhance anti-tumor immune responses. By integrating genetic mutations and immunologic insights, this review outlines a framework for developing more precise and effective immunotherapies for AML.